SKRINING FITOKIMIA DAN PROFIL KLT DARI FRAKSI N-HEKSANA DAN ETIL ASETAT PADA KULIT Pithecellobium jiringa (Jack) Prain - Ermi Abriyani; Lia Fikayuniar; Syifa Fauziah; Lulu Melinda (Jurnal Buana Farma, 2022)
Jengkol (Pithecellobium jiringa (Jack) Prain) is a plant that is very often used as a popular processed food ingredient. Based on previous research that the seeds and rind of jengkol have a hypoglycemic effect and reduce glucose levels, and other ingredients are alkaloids, saponins, quinone and flavonoids. This study aims to determine the content of secondary metabolite compounds and the TLC profile contained in the rind of jengkol at fractionation of n-hexane and ethyl acetate. The methods are screening phytochemical, column chromatography, and the TLC. The phytochemical test showed that the rind of jengkol contained terpenoid, flavonoid and saponin compounds. Fraction A was shown spot bluish-green with Rf value 0,64 by the TLC test. The result of the TLC test was indicated to- saponin compound which is characterized by the presence of foam. The result of ethyl acetate fractionation was shown as light blue on The TLC chromatogram with an Rf value of 0,47 which is characterized flavonoid test.